MODERN MEANS OF ELECTRONIC PROCESSING OF SOCIO-ECONOMIC INFORMATION - M. Bogdanova (Publishing House of the State University of Management, 2017)
The article analyzes most popular software packages for statistical analysis of economic information, identified their merits and demerits, developed recommendations for choice of statistical packages